2021
DOI: 10.1186/s12875-021-01484-y
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of provider competencies and current training for prevention and management of obesity among family medicine residency programs: a cross-sectional survey

Abstract: Background U.S. physicians lack training in caring for patients with obesity. For family medicine, the newly developed Obesity Medicine Education Collaborative (OMEC) competencies provide an opportunity to compare current training with widely accepted standards. We aimed to evaluate the current state of obesity training in family medicine residency programs. Methods We conducted a study consisting of a cross-sectional survey of U.S. family medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Recommendations for teaching obesity bias, include educating learners about the complexities and biological processes involved in weight issues, as well as removing personal blame for weight gain [ 10 , 20 ]. It has long been noted that there is a deficit in obesity education in primary care residencies, and it has been challenging to implement obesity medicine curricula to address these issues [ 21 , 22 ]. An already crowded didactic schedule, limited faculty knowledge about obesity, and negative attitudes about obesity as a disease have been highlighted as potential barriers to implementation of obesity curricula [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations for teaching obesity bias, include educating learners about the complexities and biological processes involved in weight issues, as well as removing personal blame for weight gain [ 10 , 20 ]. It has long been noted that there is a deficit in obesity education in primary care residencies, and it has been challenging to implement obesity medicine curricula to address these issues [ 21 , 22 ]. An already crowded didactic schedule, limited faculty knowledge about obesity, and negative attitudes about obesity as a disease have been highlighted as potential barriers to implementation of obesity curricula [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of validated teaching material for obesity bias, especially regarding implicit biases, and few programs have implemented any instruction around the subject of obesity bias [ 20 , 23 ]. Efficient and effective educational materials for students and residents could help overcome educational deficiencies [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to 2018, fewer programme directors in this survey assessed their residents as fairly or very prepared to provide high quality obesity care (74% vs. 58%, p = .016). 14 Residents in programmes with 1+ ABOM-certified faculty member were more likely to be very prepared to provide medical care compared to those without ABOM-certified faculty members (18% vs. 7.8% p = .047).…”
Section: Resultsmentioning
confidence: 94%
“…13 A 2018 study demonstrated that future family physicians are ill-prepared to provide comprehensive, team-based obesity care, with the majority of Family Medicine programme directors reporting their graduates to be unprepared to manage obesity. 14 The Obesity Medicine Education Collaborative (OMEC) published obesity competencies in 2019 to guide and assess educational outcomes, and efforts are ongoing to improve the quality of medical school training in the care of people with obesity. 15 These limitation in formal obesity education have led over 1700 US family physicians to seek additional expertise and board certification through the American Board of Obesity Medicine (ABOM) (American Board of Obesity Medicine, personal communication, August 26, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies may be due to the curriculum expert's familiarity with PA content in their program. By contrast, in the United States, 52% of family medicine programs were prepared to incorporate PA to a great extent in obesity prevention and management training (Orjuela-Grimm, Butsch, Bhatt-Carreño, Smolarz, & Rao, 2021). Unique to our study is that many Canadian FM programs explained they teach specifically to the CFPC priority topic areas and that some residents learn the benefits of PA, how to assess PA, prescribe PA, refer for PA, and document PA information in EMRs.…”
Section: Discussionmentioning
confidence: 96%